Issues and channels of China-Australia cultural industries' going out' in the era of digital creative industries (Translated into Chinese) - Keane, Michael (2018)
This paper describes how Australia media and culture is seeking to ‘go out’ to China, and how it is seeking out new opportunities, partners and channels. The discussion looks at both sides of the equation: cultural creativity (the film and television industries) and the technological domain (digital startups). In the first section the paper identifies how we might use social media analysis to evaluate the relative successes and failures of media ventures. The second section shows how government in Australia is making the process of working in China more feasible in the digital technology sectors. The final section returns to the question of how to promote cultural trade, this time for the benefit of China. Will the integration of culture and technology provide greater opportunities for China’s culture to go out?